Independent Component Analysis of Edge Information for Face Recognition - Karande, Kailash Jagannath (SpringerBriefs in Applied Sciences and Technology,, 2014)
The book presents research work on face recognition using edge information as features for face recognition with ICA algorithms.Â The independent components are extracted from edge information. These independent components are used with classifiers to match the facial images for recognition purpose. In their study, authors have explored Canny and LOG edge detectors as standard edge detection methods. Oriented Laplacian of Gaussian (OLOG) method is explored to extract the edge information with different orientations of Laplacian pyramid. Multiscale wavelet model for edge detection is also proposed to extract edge information. The book provides insights for advance research work in the area of image processing and biometrics.